Eksplorasi Kinerja Karyawan Berdasarkan Motivasi Kerja Serta Disiplin Kerja - Ginting, Windy Indriyani Br; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to reverse-examine the effect of the variables of work motivation with work discipline, both partially and simultaneously, on the performance of Credit Union (CU) employees in Dolat Rayat District. This type of research is causal quantitative using a data collection method in the form of a questionnaire, but first tested for validity and reliability. The number of samples used is 40 respondents. The sampling technique used is a multiple sample technique. The data analysis techniques used are multiple linear regression analysis, classical assumption tests, hypothesis t-tests, and hypothesis F-tests. The results of this study indicate: (1) there is a positive and partially significant effect of work motivation on the performance of CU employees in the Dolat Rayat District as indicated by the t-count value of the X1 variable of 5.154 and a significance value of 0.000 <0.05 (2) there is an influence positive and partially significant from work discipline to the performance of CU employees in Dolat Rayat District as indicated by the t-count value of the X2 variable of three,791 and a significance value of 0.001 <0.05 (3) there is a simultaneous significant effect of work motivation and discipline work on the performance of CU employees in Dolat Rayat Subdistrict as indicated by the F-count values ​​of the variables X1 and X2 of 14,837 and a significance value of 0.000 <0.05.